Prevalence of prehypertension and hypertension among the adults in South Asia: A multinomial logit model - Rahut, Dil Bahadur; Mishra, Raman; Sonobe, Tetsushi; Timilsina, Raja Rajendra (Frontiers in Public Health, 2023)
Hypertension has been the most common non-communicable disease in low and middle-income countries for the past two decades, increasing cardiovascular and renal disease risk. Urbanization, aging, dietary and lifestyle changes, high illiteracy rates, poor access to health facilities, poverty, high costs of drugs, and social stress have contributed to an increase in the prevalence of hypertension in developing countries. Nonetheless, little is known about the comprehensive risk factors associated with prehypertension and hypertension among economically active adult populations of South Asia, such as India, Nepal, and Bangladesh. This paper uses the Demographic and Health Survey data of 637,396 individuals from India (2019–21), 8,924 from Nepal (2016), and 8,613 from Bangladesh (2017–18) to examine the prevalence and driver of prehypertension and hypertension. We analyze the prevalence of prehypertension because it leads to hypertension and is directly related to cardiovascular disease, and many people live with it for prolonged periods without realizing it. The paper finds, among other things, that the prevalence of prehypertension and hypertension among adults (18–49 years) was 43.2% and 14.9% in India, 35.1% and 19.8% in Bangladesh, and 25.2% and 13.8% in Nepal, respectively. Better educated, wealthy individuals living in urban areas of developing economies in the South Asian region are more likely to have prehypertension and hypertension. The paper suggests the urgent need to launch preventive programs to reduce prehypertension before it develops to be hypertension as a precautionary measure. Thus, such measures shall help to prevent hypertension, thereby improving the overall well-being of individuals and families.